From trauma to transmission: exploring the intersection of adversity, substance use, and HIV risk in women's life histories - Nora S. West; Frank Kussaga; Alex Rittenhouse; Brenice Duroseau; Deja Knight; Jessie Mbwambo; Samuel Likindikoki; Haneefa T. Saleem (BMC, 2023)
Abstract Background At increased risk for poor health outcomes, physical and/or sexual violence, and onward transmission of HIV, women who use drugs and are living with HIV (WWUDHIV) are vulnerable and in need of services. Understanding the role of trauma across their life history may offer insights into HIV and drug use prevention and opportunities for intervention. We explored trauma and drug use among WWUDHIV in Dar es Salaam, Tanzania. Methods We conducted in-depth interviews with 30 WWUDHIV from January-March 2019. Interviewers used semi-structured interview guides and asked questions about the life history as related to drug use. Interviews were audio recorded, transcribed, translated, coded, and life histories charted. We utilized content analysis. Results Participants described death of family members as traumatic catalysts for drug use. Sexual partners early in their life history were often the point of introduction to drugs and source of HIV acquisition. Death of partners was present across many life histories and was a traumatic event negatively influencing life trajectories, including start of sex work for survival or to support drug use. Sex work in-turn often led to traumatic events including sexual and/or physical violence. HIV diagnosis for many participants followed the start of drug use, frequently occurred during pregnancy or severe illness and was described by most participants as a trauma. Despite this, particularly during pregnancy, HIV diagnosis was a turning point for some participant's desire to engage in drug use treatment. Traumatic events were often cumulative and regularly described as catalysts for poor mental health that could lead to new or increased drug use for coping. Conclusions These findings suggest trauma is common in the life history of WWUDHIV and has negative impacts on drug use and HIV vulnerability. Our life history charting highlights the cumulative and cyclical nature of trauma and drug use in this population. This study allows for better understanding of trauma, drug use, and HIV prevention, which offers opportunities for intervention among a group with limited access to services: during adolescence for orphaned youth, following the death of a child or partner, and when vulnerable women engage with the health system (HIV diagnosis, pregnancy, illness).